2018
DOI: 10.1108/jcm-01-2018-2537
|View full text |Cite
|
Sign up to set email alerts
|

Climate change risk perceptions among green conscious young consumers: implications for green commodity marketing

Abstract: Purpose This study aims to explore how young adults understand the climate change problem. It also explores whether environmental paradigms explain how young adults perceive climate change risks in their everyday green conscious behavior. Design/methodology/approach This interpretive research draws on in-depth interviews with 20 young Australians (aged between 19-25 years) who engage in green conscious behavior. Findings Three thematic categories (“non-local” climate change risk, oscillation between enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Paul and Rana (2012) also observed that environmental knowledge leads to green awareness and is an antecedent to purchasing intention. Green awareness positively influences green attitude (Lim et al., 2013), but expected environmental risks influence it negatively (Perera & Hewege, 2018). This risk creates a gap between the attitude and actual green purchase behaviour of consumers.…”
Section: Results From Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Paul and Rana (2012) also observed that environmental knowledge leads to green awareness and is an antecedent to purchasing intention. Green awareness positively influences green attitude (Lim et al., 2013), but expected environmental risks influence it negatively (Perera & Hewege, 2018). This risk creates a gap between the attitude and actual green purchase behaviour of consumers.…”
Section: Results From Literature Reviewmentioning
confidence: 99%
“…Such changes have been observed across countries such as Greece, Pakistan, Malaysia and India. Although, eco‐consciousness has increased in Asian countries, but perceived risks have restricted it in Australia and Canada (Perera & Hewege, 2018). Despite an increase in consciousness, an increase in demand for green products has not been noticed in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognized as the emerging market for green behaviors (Nguyen et al , 2018), young consumers are the target interest of this study as they are known to be receptive to change and innovation and are aware of the plight of the existing environment (Uddin and Khan, 2018). Further, proponents of environmental conservation and protection are likely to be younger (Perera and Hewege, 2018; Tong and Su, 2018), and “young consumers have substantial potential to be key stakeholders in the development of sustainable consumption patterns” (Gupta et al , 2019, p. 192). Despite being dubbed as the consumers of tomorrow, there have been limited studies on Generation Z and sustainable consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous negative impacts of climate change on the environment have attracted the attention of stakeholders to take intervening action to mitigate its impact (Perera and Hewege, 2018; Saleem et al , 2021; Tong and Su, 2018). Globally, initiatives are drawn up by international organizations such as the United Nations through their Sustainable Development Goals (UNSDG), which outlines 17 goals such as climate action, responsible consumption and production, sustainable cities and communities, and affordable, clean energy, among others (UNSDG, 2021).…”
Section: Introductionmentioning
confidence: 99%